The Challenge of HIV-1 Antiretroviral Resistance in Africa in the Era of HAART - Sendagire, Hakim; Easterbrook, Philippa J.; Nankya, Immaculate; Arts, Eric; Thomas, David; Reynolds, Steven J. (AIDS reviews, 2009)
Antiretroviral therapy programs in Africa are currently providing treatment for almost two million people. The long-term success of large scale antiretroviral therapy programs in sub-Saharan Africa remains uncertain because of the limited information currently available on rates of virologic failure and selection for drug-resistant variants in the different HIV subtypes. This article provides a comprehensive review of the published literature on the prevalence of primary and secondary HIV drug resistance with different subtypes and in various settings across sub-Saharan Africa.
Keywords: Antiretroviral therapy, ART, Resistance, Africa, Subtypes, Phenotypic, Genotypic